Efektivitas Terapi Audio Visual (Film Kartun) Terhadap Kecemasan Pada Anak Usia Prasekolah - Sri Ekasaputri; A. Arniyanti (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Introduction: Anxiety is a subjective experience of feeling uncomfortable that arises from unspecified causes. Pharmacological therapy to reduce anxiety is the administration of anti-anxiety drugs (alprazolam triazole benzodiazepine) 0.5 mg 3 times a day. One of the distraction techniques that can be used to reduce anxiety in children undergoing surgery is the use of audio-visual therapy (cartoon films). Objective: The purpose of this study was to determine the effectiveness of audio-visual therapy (cartoon films) on anxiety in preschoolers. Method: This study explores quantitative evidence published in electronic databases such as Pubmed, and google scholar. By using a journal search strategy, the final results are 3 articles which are the main references in the preparation of this research. Results: From the three articles reviewed, it can be seen a significant effect in reducing anxiety levels in preschool children after audio-visual therapy intervention. Conclusion: That audio-visual therapy (cartoon films) is effective in reducing anxiety levels in children aged 3-6 years